(untitled) (The Research of Medical Science Review, 2024)
Breakfast is an essential meal contributing to overall health, cognitive function, and dietary adequacy. In Peshawar, Khyber Pakhtunkhwa, breakfast choices are influenced by cultural traditions, socioeconomic factors, and nutritional awareness. This study examines how these elements shape breakfast consumption patterns. A cross-sectional approach was utilized, collecting data from 400 households. Nutritional composition, affordability, accessibility, and dietary habits were analyzed through descriptive and inferential statistics. Findings highlight the dominance of traditional foods, with economic constraints and time limitations influencing meal selection. Macronutrient composition varied significantly across breakfast types, with high-calorie and carbohydrate-dense meals being more common among lower-income groups. ANOVA results confirmed statistically significant differences in nutrient intake across age groups (F =15647.73, p < 0.0001), while Shapiro-Wilk and Levene’s tests indicated normal distribution but unequal variances among nutrients. The chi-square test revealed strong associations between socioeconomic status and dietary choices (p < 0.05). Cultural influences played a crucial role, with traditional meals like Haleem and Omelette being widely consumed, while modern dietary shifts were observed among younger and working individuals. The study underscores the need for targeted nutritional education, policy interventions, and improved access to balanced breakfast options to promote healthier dietary habits. Future research should explore long-term dietary trends and evaluate the effectiveness of public health initiatives aimed at improving breakfast consumption patterns in Pakistan.